2023
DOI: 10.1109/tbme.2022.3187874
|View full text |Cite
|
Sign up to set email alerts
|

Global ECG Classification by Self-Operational Neural Networks With Feature Injection

Abstract: Objective: Global (inter-patient) ECG classification for arrhythmia detection over Electrocardiogram (ECG) signal is a challenging task for both humans and machines. Automating this process with utmost accuracy is, therefore, highly desirable due to the advent of wearable ECG sensors. However, even with numerous deep learning approaches proposed recently, there is still a notable gap in the performance of global and patientspecific ECG classification performance. Methods: In this study, we propose a novel appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 64 publications
(93 reference statements)
0
12
0
Order By: Relevance
“…The best performances for each evaluation index are shown in bold font. It is worth noting that the algorithm proposed by Zahid et al ( Zahid et al, 2022 ) showed the best specificity 99.83% for N heartbeat type, and Sellami et al ( Sellami and Hwang, 2019 ) presented the higher accuracy 99.99% and specificity 89.54% for S heartbeat type. However, the specificity and accuracy are not the reasonable measure indexes in imbalanced dataset as shown in Table 8 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The best performances for each evaluation index are shown in bold font. It is worth noting that the algorithm proposed by Zahid et al ( Zahid et al, 2022 ) showed the best specificity 99.83% for N heartbeat type, and Sellami et al ( Sellami and Hwang, 2019 ) presented the higher accuracy 99.99% and specificity 89.54% for S heartbeat type. However, the specificity and accuracy are not the reasonable measure indexes in imbalanced dataset as shown in Table 8 .…”
Section: Discussionmentioning
confidence: 96%
“…Prabhakararao et al ( Prabhakararao and Dandapat, 2021 ) designed a classifier based multiple scale-dependent deep convolutional neural networks with different receptive fields for arrhythmia classification, the model showed impressive performance (averaged 84.5% F 1 score on PTBXL-2020 dataset and 88.3% F 1 score on CinC-2017 dataset) and generalization ability, and then made it suitable for arrhythmia monitoring applications. Zahid et al ( Zahid et al, 2022 ) used MIT-BIH arrhythmia dataset and proposed a novel model combined temporal feature based on RR interval and learned features to classify arrhythmia, the F 1 score is 99.15% for super-ventricular ectopic beats and 95.2% for ventricular-ectopic beats. Khatibi et al ( Khatibi and Rabinezhadsadatmahaleh, 2019 ) proposed a novel feature engineering method based on deep learning and K-NNs showing a good performance to classify heartbeat.…”
Section: Introductionmentioning
confidence: 99%
“…Since CAT is to identify and represent smoking-related brain features, we use three classical ML-based methods (e.g., KNN [7], RF [8], and SVM [9]) and seven well-known DL-based approaches (e.g., Xception [17], VGG 19 [18], VGG 16 [19], ResNet 18 [20], Mobile [21], Shuffle [22], and DenseNet [23]) as baselines for comparisons. For the five datasets, the training model of each baseline strategy is re-trained, to provide optimal results for fair comparisons.…”
Section: Baseline Methods and Metricsmentioning
confidence: 99%
“…As for MARD, it consists of 48 2-leads recordings and each recording is sampled with a frequency of 360 Hz with the duration of 30 min [32]. Further, we will de-110 sample the recordings of MARD into 250 Hz for data consistency dividing them into 2 s fragments [33,34], implement denoising by wavelet transform strategy and carry out Z-score normalization on filtered ECG fragments for accelerating convergence [45]. Table 1 shows details of ECG fragments in this research.…”
Section: Databasementioning
confidence: 99%